PEMBELAJARAN TEORI SASTRA BERBASIS DIGITAL DI ERA PANDEMI - Ahmad Bahtiar (Universitas Singaperbangsa Karawang, 2022)
ABSTRACT The presence of the corona virus or Covid-19 has made life not as normal as it used to be. Some of the impacts given by Covid-19 are quite influential, one of which is in the education sector. This influence has an impact that makes educators change existing teaching strategies into digital-based teaching strategies in the pandemic era. Lecturers feel that using rote-based theoretical learning techniques makes the scope of the class ineffective but does not produce students who have critical and creative thinking in the current pandemic era. The purpose of this research entitled